MPS 16-04 EVALUATION OF LOCAL CAROTID STIFFNESS AND WALL-TO-LUMEN RATIO OF RETINAL ARTERIOLES IN NORMOTENSIVE SUBJECTS AND HYPERTENSIVE PATIENTS. (September 2016) - Caletti, Stefano; Paini, Anna; Salvetti, Massimo; Rizzoni, Damiano; De Ciuceis, Carolina; Rosei, Claudia Agabiti; Bertacchini, Fabio; Rubagotti, Giulia; Colonetti, Efrem; Casella, Elisa; Muiesan, Maria Lorenza; Rosei, Enrico Agabiti
Abstract : Objective: Wall-to-lumen ratio of retinal arterioles (W/L) might serve as an in-vivo parameter of microvascular damage. Few data are available on the correlation between local stiffness, evaluated at carotid artery level, and the presence of retinal abnormalities, assessed by arteriolar/venular ratio. Aim of the study was to analyse the correlation between carotid stiffness (CS) and W/L of retinal arterioles. Design and Method: Methods: 227 subjects (56% female, age 55 ± 4 years, 48% hypertensives, 30% treated) underwent laboratory examinations, clinic BP measurement, carotid-femoral pulse wave velocity (aoPWV) and W/L ratio measurement. CS was determined from the relative stroke change in diameter (measured with a high-resolution echotracking system) and carotid pulse pressure (measured with applanation tonometry). Results: both W/L and CS were significantly related with clinic SBP (r = 0.17, p < 0.05 and r = 0.50, p < 0.001), clinic PP (r = 0.22, p < 0.001 and r = 0.55, p < 0.001), carotid SBP (r = 0.18, p < 0.05 and r = 0.51, p < 0.001) and with carotid PP (r = 0.24, p < 0.001 and r = 0.56, p < 0.001). W/L was not significantly related with age and laboratory data while a positive correlation was observed between W/L and CS (r = 0.18, p < 0.005). At multivariate analysis CS, but not aoPWV, remained independently associated with W/L. Conclusions: In this large group of hypertensives and normotensives local carotid stiffness represents the main determinant of wall to lumen ratio of retinal arterioles.